A Study on Solubilization of Poorly Soluble Drugs by Cyclodextrins and Micelles: Complexation and Binding Characteristics of Sulfamethoxazole and Trimethoprim - ÇALIŞKAN SALİHİ, ELİF; CANTÜRK TALMAN, REMZİYE YEŞİM; GÖKTÜRK, SİNEM (HINDAWI LTD, 2012)
The present study is focused on the characterization of solubilization of poorly soluble drugs, that is, sulfamethoxazole (SMX) and trimethoprim (TMP) by cyclodextrins (alpha-, beta-, and gamma-CDs) and anionic surfactant sodium dodecyl sulfate (SDS). The phase solubility diagrams drawn from UV spectral measurements are of the A(L) type and indicate an enhancement of SMX and TMP solubility in the presence of CDs. Complex formation tendency of TMP with CDs followed the order: gamma-CD > beta-CD > alpha-C. However, the complex formation constant values, for SMX-CD system yielded the different affinity and follow the order: beta-CD > gamma-CD > alpha-CD. With taking into consideration of solubilization capacity of SDS micelles, it has been found that the solubility enhancement of TMP is much higher than that of SMX in the presence of SDS micelles. The binding constants of SMX and TMP obtained from the Benesi-Hildebrand equation are also confirmed by the estimated surface properties of SDS, employing the surface tension measurements. In order to elucidate the solubilization characteristics the surface tension measurements were also performed for nonionic surfactant Triton X-100. Polarity of the microenvironment and probable location of SMX and TMP were also discussed in the presence of various organic solvents.
Keywords: PHARMACEUTICAL APPLICATIONS; INCLUSION COMPLEXATION; BETA-CYCLODEXTRIN; SURFACTANTS; FUTURE; DERIVATIVES; MEMBRANES; BEHAVIOR; SYSTEM